Efektivitas Model Problem Based Learning Terhadap Peningkatan Sikap Toleransi Siswa di Sekolah Dasar Systematic Literature Review - Agus Susanto; Yoyo Zakaria Ansori; Wina Dwi Puspitasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to assess the effectiveness of the Problem-Based Learning (PBL) model in improving tolerance in elementary school students. The study used the Systematic Literature Review (SLR) method with PRISMA guidelines as a reference in the process of searching, filtering, and analyzing articles. Data sources were obtained from various national scientific databases with articles published in 2020–2026. The selection results showed that there were 15 articles that met the inclusion criteria and were used in this study. Based on the analysis results, the implementation of PBL has been proven to improve students' tolerance through discussion activities, group work, and collaborative problem solving. In addition to increasing tolerance, this model also supports the development of communication skills, collaboration, social interaction, empathy, and an attitude of respect for diversity. The majority of articles analyzed used experimental methods and Classroom Action Research (CAR), and were applied to Pancasila Education and Mathematics subjects. Although the implementation of PBL requires more time and teacher skills in managing learning, this model is considered effective in creating active learning and supporting the strengthening of elementary school students' character.